ABDOMINAL TUBERCULOSIS AN EXPERIENCE AT AYUB TEACHING HOSPITAL ABBOTTABAD - Khan, Ishtiaq Ali; Khattak, Irfan -ud-din; Asif, Saadia; Nasir, Mohammad; Rehman, Zia -ur- (Journal of Ayub Medical College Abbottabad, 2008)
Background: Abdominal tuberculosis is one of the common diseases in our country. This study was performed at Surgical A Unit Ayub Teaching Hospital Abbottabad from August 2006 to December 2007 to asses the clinical presentation of abdominal tuberculosis and its management. Methods: All patients presenting to outpatient department with clinical feature suggestive of abdominal tuberculosis were included in the study. They were investigated. On the basis of clinical presentation, patients were divided in two groups. Patients with acute abdomen (peritonitis, intestinal obstruction) were prepared for laparotomy and operated upon. Required surgical procedure performed and tissue diagnosis was obtained. Patients with sub-acute obstruction, chronic pain abdomen and mass abdomen with out peritonism were managed conservatively. These patients were started on anti TB drugs on the basis of clinical and laboratory assessment. Empiric therapeutic trial was conducted for at least for 3 months with standard four drugs regimen. They were sent home on 9 month course of Anti TB drugs and were advised to come for follow up twice a month. On reassessment good clinical response was considered abdominal tuberculosis and anti TB continued with monthly follow up. In case of no response patients were operated. Required surgical intervention performed and tissue was taken to establish diagnosis. Detailed history, family history, examination findings, results of investigations, operative findings of the histologically proven cases of abdominal tuberculosis were recorded on a separate proforma and analyzed. Results: Amongst 76 patients majority were females 52 (68.4%). Most of the patients were young with mean age of 34 years. Abdominal pain was the most common presentation 73 (96%) followed by fever and anorexia. Tender lower abdomen as found in 53 (70%) patients and mass abdomen was found in 35 (46%). Family history of TB was present in 20 (26%). Fifty three (70%) patients underwent laparotomy. Bands and adhesion was the most frequent finding on laparotomy. Conclusion: Abdominal TB is more common in female and abdominal pain fever and nausea are the most common presentations. Keywords: Abdominal tuberculosis, abdominal mass, exploratory laparotomy